Visualizing the change of “viewpoints” in 3D virtual art exhibition - Kazuki Matsumoto; Takeshi Okada (i-Perception, 2025)
This study focuses on the process of viewers’ engagement with artwork in virtual spaces. Specifically, we propose a methodology that combines two approaches: (a) measuring movements within virtual spaces, and (b) using non-immersive virtual reality. We attempt to demonstrate the effectiveness of this methodology through experimentation. In the experiment, we recorded the exploration of sculptures in virtual spaces of 317 participants using a newly developed system (Virtual Exhibition Space for Tracking and Analyzing system). Results from multiple statistical analyses, including hierarchical Bayesian analysis, indicated differences in view-angles and distances traveled while viewing the artworks under different experimental conditions (where different instructions were given prior to viewing). These findings support the theoretical expectation that the “mode” of viewing artworks is influenced by instructions given before viewing, which is further corroborated by the observed differences in the pattern of psychological measurements between conditions. Based on previous research and these experimental results, we discuss the effectiveness and generalizability of our methodology in capturing variations in the art-viewing process as a tool for studying art-viewing behavior not only in virtual but also in real environments.